Automated classification and quantification of F-actin-containing ruffles in confocal micrographs. (June 2006) - Yi, Qing; Coppolino, Marc G.
Membrane ruffles are actin-rich protrusions of the plasma membrane that can be observed on the surface of many cell types. Phase contrast and fluorescent microscopy are widely used in the analysis of ruffles, which are commonly identified in cells stained withfluores-cently labeled phalloidin. Currently, comparison of cellular ruffle formation under different experimental conditions is generally qualitative or semiquantitative. Ruffle structures are often defined using manual tracing and thresholding methods. Here, we report the rapid and accurate segmentation of ruffles from two-dimensional confocal projections of cells using an automated method based on well-established image processing and analysis methods. Line-shaped ruffles were detected using line detectors and were then separated from the filtered images. Automated categorizing of the segmented line structures enabled accurate quantification of the ruffles. This automated approach is efficient and reliable and hence can serve as a powerful tool in studies of the mechanism of ruffle formation.